THE EFFECT OF PROFITABILITY ON FIRM VALUE MEDIATED BY TAX AVOIDANCE IN MANUFACTURING COMPANIES LISTED ON THE IDX - Khairunnizha; Ismail Badollahi; saida said (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2025)
This research is driven by the critical importance of firm value as a fundamental indicator for investors in assessing a company's prospects, with profitability serving as a primary catalyst. Given the inconsistent findings in prior literature regarding the role of tax avoidance, this study evaluates its function as a mediating variable. Utilizing a quantitative approach focused on manufacturing firms listed on the Indonesia Stock Exchange, and employing path analysis via Eviews, the results demonstrate that profitability exerts a significant positive influence on both firm value and tax policies. Crucially, the study confirms that tax avoidance acts as a partial mediator; this indicates that market valuation increases not only through direct profit growth but also through strategic tax efficiency. Consequently, management is encouraged to integrate legal tax planning into financial strategies to bolster cash flow, while investors should scrutinize tax management effectiveness as a vital sign of managerial competence in sustaining long-term firm value.